Evaluation of pseudophakic cystoid macular edema using optical coherence tomography angiography. Issue 2 (March 2018) - Serra, Rita; Sellam, Alexandre; Coscas, Florence; Bruyère, Elsa; Sieiro, André; Coscas, Gabriel J.; Souied, Eric H.
Purpose: To compare the optical coherence tomography angiography (OCT-A) findings of the superficial capillary plexus (SCP) and deep capillary plexus (DCP) in eyes with pseudophakic cystoid macular edema (PCME) with those of fluorescein angiography (FA) and spectral-domain optical coherence tomography (SD-OCT) and to compare PCME vascular density values of the SCP and DCP with those of healthy eyes. Methods: In this retrospective observational study, 13 eyes (12 patients) with PCME underwent comprehensive ophthalmologic examinations including visual acuity, FA, SD-OCT, and OCT-A. The vascular density of the SCP and DCP were measured using AngioAnalytics software in all PCME eyes and compared with 46 healthy eyes of 25 subjects. Results: In patients with PCME, at the level of SCP, the mean vascular density in the whole en face image was 44.48 ± 3.61% while it was 50.27 ± 5.30% at the level of the DCP. In contrast, the vascular density in the whole en face image was 50.35 ± 3.22 at the level of SCP while it was 56.15 ± 3.28 at the level of DCP in 46 healthy eyes of 25 subjects. The vascular density of patients with PCME was significantly lower than in healthy subjects at the SCP (p<0.0001) and at the DCP (p<0.0001). Conclusion: We report the OCT-A appearance of PCME and vascular density map with values that can be easily interpreted for quantitative evaluation of retina perfusion status using OCT-A. This approach might be the first step in helping us fully understand the pathophysiologic mechanisms underlying PCME.